Presqu’un siècle de géomorphologie dans le Bulletin de l’Association de Géographes Français - Christian Giusti (Bulletin de l’Association de Géographes Français, 2020)
The Bulletin of the Association of French Geographers has now been fully digitized. Online issues from 1924 to 2012 are provided by Persée, later ones by Open Edition. An analysis of more than three thousand articles, among which a thousand deal with geomorphology — whether in a narrow (i.e. structural and climatic geomorphology) or a wider sense that includes environmental geography and anthropogeomorphology — documents the gradual replacement of the Davisian cycle of erosion as an overarching paradigm by the model of erosion systems advocated by Cholley and Tricart from the 1950s onwards. The naturalistic study of planet Earth is also shown to have gradually given way to an anthropocentric frame of reference, with likewise a shift in perspective from geological deep time to historic time. The latter spans the “longue durée” of civilizations as addressed in geoarchaeology to the current affairs of modern societies, dealing for example with the geomorphological aspects of so-called natural hazards. This longitudinal study of the journal’s output evidences profound transformations in the profile of geomorphology as a discipline. Broadening geomorphology to new themes, however, has also resulted in reducing its scope to technical approaches and in somewhat diluting its identity in the melting pot of environmental geography.